Delineation of a complex karyotypic rearrangement by microdissection and CGH in a family affected with split foot. Issue 6 (1st June 2000) - Weimer, Jörg; Kiechle, Marion; Wiedemann, Ute; Tönnies, Holger; Neitzel, Heidemarie; Ruhenstroth, Eberhard; Ovens-Raeder, Angela; Arnold, Norbert
Abstract : We report on a male patient and members of his family with additional material in chromosome 3. This derivative chromosome 3 was transmitted from his mother who had a complex rearrangement between chromosomes 2, 3, and 7. It was possible to delineate her chromosomal rearrangement by microdissection and reverse painting and to exclude these aberrations from being responsible for neonatal deaths and several abortions in this family. Two members of this family suffer from ectrodactyly or split hand/foot malformations (SHFM) of the feet which possibly correlates with the derivative chromosome 7 containing a breakpoint in the SHFM1 critical region involving several homeobox genes.